2019
DOI: 10.7759/cureus.6302
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Perceptions Regarding Basic Life Support Among Teachers in Training

Abstract: Background Cardiac arrests may occur anytime, anywhere and to anyone including learners at schools. Teachers have a moral obligation to care for learners while on the school premises. Outcomes after cardiac arrest are better when the first-responder possesses adequate knowledge and skill in basic life support (BLS) and cardiopulmonary resuscitation (CPR). The aim of this study was to assess the knowledge, attitudes and perceptions of student-teachers pertaining to BLS. Methods This was a self-administered, que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 21 publications
8
34
0
2
Order By: Relevance
“…As for S-CPR, the main obstacle was lack of confidence (28.7%) as well, especially among women (31.5%). The second difficulty, fear of disease transmission (22.9%), covered a large percentage (94%) in Sweden 25 and 58.9% in South Africa, 26 but in Crimea only about 2.1%-9.7% of people worried about disease transmission. 21 These differences may stem from cultural and regional epidemiological differences such as the high HIV prevalence in South Africa.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…As for S-CPR, the main obstacle was lack of confidence (28.7%) as well, especially among women (31.5%). The second difficulty, fear of disease transmission (22.9%), covered a large percentage (94%) in Sweden 25 and 58.9% in South Africa, 26 but in Crimea only about 2.1%-9.7% of people worried about disease transmission. 21 These differences may stem from cultural and regional epidemiological differences such as the high HIV prevalence in South Africa.…”
Section: Open Accessmentioning
confidence: 99%
“…37 The primary reasons for not receiving CPR training were not knowing where to study and no free training locations, which were similar to those noted in a previous investigation. 26 Since 2015, AHA has recommended online training as resources for teaching and learning. Students take video-based courses before simulation training, with instructors providing feedback to standardise their performing.…”
Section: Open Accessmentioning
confidence: 99%
“…This finding is consistent with some previous prospective study on senior undergraduate student-teachers enrolled at South African university, which found that the student-teachers surveyed displayed poor knowledge and perceptions but positive attitudes with regards to practice of CPR and BLS, and this suggested that formal CPR training was supposed to be part of the curriculum for teachers. 19 The BLS training increases laypersons’ confidence and willingness to perform bystander CPR on a stranger. 20 21…”
Section: Discussionmentioning
confidence: 99%
“…In USA BLS courses has been part of training of health care team since 1966 however, in developing countries it is not a part of mandatory training. Importance of comprehensive and up to date BLS training is even an essential requirement for laypersons according to American heart Association (AHA) chain of survival considering the fact health professionals proficiency and competency on BLS cannot be overlooked [1].…”
Section: Introductionmentioning
confidence: 99%